Crossing boundaries: facilitating conceptual development in relation to culture in an English for academic purposes course - Dison, Arona (Rhodes University, Faculty of Humanities, Department of English Language and Linguistics, 1998)
This research was undertaken as the first cycle of an action research project. The aim was to develop a course within the English Language 1 for Academic Purposes (ELAP) course at Rhodes University, which would facilitate the conceptual development of students in relation to the topic of Culture. The implementation of the course was researched, using students' writing, interviews, staff meeting discussions and video-taping of certain classes. Ten students volunteered to 'be researched'. The types of initial 'commonsense' understandings of culture held by students are outlined and the conceptual development which they underwent in relation to Culture is examined. Students' perceptions of the approaches to learning required in ELAP and the Culture course in particular are explored. The involvement of the ELAP tutors in the course and in the research was a learning experience for them, and this became-another focus of the research. The findings of the research support the argument for using challenging subject matter in English for Academic Purposes (EAP) courses, provided that the learning process is carefully scaffolded. An underlying assumption is that ways of thinking and learning in university courses need to be explicitly taught to students and the study concludes that lecturers of mainstream courses could also learn from the findings of research such as this. The study also shows the potential power of participatory action research to involve practitioners in research and enhance their understandings of aspects of their practice. Finally, it notes the need to value subtle developments in students and to see them as being part of a longer term process.
Keywords: Compensatory education -- South Africa; English language -- Study and teaching (Higher) -- Foreign speakers; English language -- Study and teaching (Higher) -- Foreign speakers -- Psychological aspects